THEORETICAL FOUNDATIONS OF LINGUOCULTUROLOGY: THE INTERRELATION BETWEEN LANGUAGE AND CULTURE - Turgunboeva Dilnoza Akmal kizi (Scholar Express Journal, 2025)
The present study explores the theoretical foundations of linguoculturology, focusing on the intrinsic interrelation between language and culture. Linguoculturology, as an interdisciplinary field, seeks to examine linguistic phenomena through the prism of cultural context, revealing how language both shapes and reflects a society’s worldview, values, and traditions. The research adopts a comprehensive qualitative approach, drawing from theoretical frameworks in linguistics, cultural studies, and cognitive science to present a holistic understanding of the mutual influence between language and culture. Special attention is given to cross-cultural comparisons and the analysis of linguistic units with cultural significance, including idioms, metaphors, and culturally marked lexemes. The findings demonstrate that language and culture are interdependent, dynamic systems, where language serves as both a product and a driver of cultural identity. Furthermore, the study underscores the necessity of incorporating linguocultural competence into language education, particularly in the era of globalization, where intercultural communication is essential. This paper aims to contribute to the broader theoretical discourse in linguoculturology by providing an in-depth, interdisciplinary perspective and suggesting avenues for future research.
Keywords: linguoculturology; language and culture; cultural identity